Demonstration Of Suicidal Behavior - Abdullayeva Mushtariy (Euro Asian Journal Publishing, 2025)
the manifestations of suicidal behavior, its developmental stages, clinical and social characteristics, diagnostics, and modern prevention methods. It emphasizes that suicide is a serious public health issue on a global scale and that its prevention requires a comprehensive approach.Also discusses the relationship between suicidal behavior and mental illnesses such as depression, schizophrenia and others.
Keywords: suicidology; suicidal behavior; depression